Authenticity and Artificiality: Juvenilia in the Twentieth and Twenty-first Centuries - Redcay, Anna (Journal of Juvenilia Studies, 2026)
This essay, part of this issue's Editor's Column on the theme "Surveying Our Spacious Field," argues that contemplating juvenilia’s attributes and our perceptions of them can, in turn, offer rewarding opportunities for reflection on our scholarly practices. The essay poses a set of queries meant to generate conversation about how we select and value juvenilia, how we frame our analysis of this literary or artistic production, and how we name our own habits of engagement with children and the works they produce.